EC internal market: An opportunity for CMEA countries? - Horst Tomann (Intereconomics, 1989)
The removal of the internal frontiers within the EC will tend to have a negative effect on trade relations between EC and CMEA countries. The implications of 1992 for trade patterns between the EC and the CMEA are examined in the following article and the role which future EC trade policy could play here is outlined.
Keywords: 330